Dextrans produced by lactic acid bacteria exhibit antiviral and immunomodulatory activity against salmonid viruses. (25th June 2015) - Nácher-Vázquez, Montserrat; Ballesteros, Natalia; Canales, Ángeles; Rodríguez Saint-Jean, Sylvia; Pérez-Prieto, Sara Isabel; Prieto, Alicia; Aznar, Rosa; López, Paloma
Highlights: Dextrans from 2 Gram positive bacteria were tested for activity vs 2 salmonid viruses. Both had in vitro activity (1.0 mg mL −1 ) vs infectious pancreatic necrosis virus. Lb. sakei dextran had best in vitro activity (500 μg mL −1 ) vs . hematopoietic necrosis virus. A range of commercial dextrans had little or no antiviral activity. Lb. sakei dextran pretreatment markedly increased survival in trout infected with either virus. Abstract: Viral infections in the aquaculture of salmonids can lead to high mortality and substantial economic losses. Thus, there is industrial interest in new molecules active against these viruses. Here we describe the production, purification, and the physicochemical and structural characterization of high molecular weight dextrans synthesized by Lactobacillus sakei MN1 and Leuconostoc mesenteroides RTF10. The purified dextrans, and commercial dextrans with molecular weights ranging from 10 to 2000 kDa, were assayed in infected BF-2 and EPC fish cell-line monolayers for antiviral activity. Only T2000 and dextrans from MN1 and RTF10 had significant antiviral activity. This was similar to results obtained against infectious pancreatic necrosis virus. However the dextran from MN1 showed ten-fold higher activity against hematopoietic necrosis virus than T2000. In vivo assays using the MN1 polymer confirmed the in vitro results and revealed immunomodulatory activity. These results together with the high levels of dextran production (2 g L −1 ) by Lb. sakei MN1, indicate the compounds potential utility as an antiviral agent in aquaculture.